Polimorfismo enzimático em Sitophilus oryzae (Coleoptera, Curculionidae) da Região Sul do Brasil - Bespalhok, Danielle das Neves (2012)
Sitophilus oryzae, (rice weevil), is a cosmopolitan species of India and considered a pest of great economic importance. In rice, S. oryzae infests wheat, oats, rye, barley, millet, canary seed, sunflower. This pest in one of the most visible threats to sustainable food production. This study aimed to estimate the genetic variability of S. oryzae in three populations, one from the State of Parana, other from Santa Catarina State and another one in Rio Grande do Sul State, based on isozyme electrophoresis, in order to provide subsidies to evolutionary studies and conservation of natural resources. For this, the technique of isozyme electrophoresis in starch gel was used for analysis of eight enzyme systems (AAT, ACP, GDH, GPI, IDH, MDH, ME and PGM). Ten loci and 18 alleles were detected. The average observed heterozygosity was 0.0091, 0.0100 and 0.0000 and the average expected heterozygosity was 0.0419, 0.0452 and 0.0000 for the populations of PR, SC and RS respectively. The percentage of polymorphic loci in populations was 30% of PR and SC 0% of the population not presenting the RS polymorphism. The average number of alleles per locus ranged from 1.4 to 1.0. The estimated values for genetic identify (I) between populations of SC and PR, PR and RS and between populations of SC and RS were I= 0.6892, I = 0.9983 and I = 0,6925, respectively. The Nei´s genetic distance were 0.3722, 0.3675 and 0.0017 for, differences between PR vs. SC, RS VS. SC and PR vs. RS respectively.